Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Beras Ketan di Pasar Induk Lambaro Kabupaten Aceh Besar - Dewi Rahmalia Ningsih; Indra Indra; Romano Romano (Jurnal Ilmiah Mahasiswa Pertanian, 2018)
The aims of research to identify factors that affect the demand for glutinous rice in Pasar Induk Lambaro District of Aceh Besar, to analyze the elasticity of demand for glutinous rice in Pasar Induk Lambaro Kabupaten Aceh Besar, and to identify glutinous rice based on the type of goods.The location of research was done by purposive sampling, has this study done in accidental sample, with a total sample of 30. The data used are primary data (consumen) in Pasar Induk Lambaro District of Aceh Besar through direct interviews using questionnaires. This study uses regression analysis of log linear regression. The result of analysis showed that the factors that influence the demand for price of glutinous rice, and situational is month of Hajj was significantly, price of black glutinous rice, income of household, and quantity of household members were not significant. Based on the value of elasticity is 2,952 showed elastic, based on cross elasticity is 0,411 showed positive value meaning that black glutinous rice is substitution product of glutinous rice and the income elasticity is 0,536 showed glutinous rice is normal product, meaning that the demand for glutinous rice will go up when income rises also. Keywords: Demand, Glutinous rice, Elasticity.